1996
DOI: 10.1037/0022-3514.70.2.321
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the State Hope Scale.

Abstract: Defining hope as a cognitive set comprising agency (belief in one's capacity to initiate and sustain actions) and pathways (belief in one's capacity to generate routes) to reach goals, the Hope Scale was developed and validated previously as a dispositional self-report measure of hope (Snyder et al., 1991). The present 4 studies were designed to develop and validate a measure of state hope. The 6-item State Hope Scale is internally consistent and reflects the theorized agency and pathways components. The relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
1,361
3
46

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,786 publications
(1,441 citation statements)
references
References 32 publications
31
1,361
3
46
Order By: Relevance
“…As such, state hope was included so as to document how it augments the prediction of cross-country achievement beyond dispositional hope. This 6-item measure of state hope comprises three agency items and three pathways items (Snyder, Sympson, et al, 1996). The items are reworded from the dispositional Hope Scale so as to tap the present tense (e.g., two agency items are "At the present time, I am energetically pursuing my goals," and "At this time, I am meeting the goals that I have set for myself;" two pathways items are "There are lots of ways around any problem that T am facing now," and "I can think of many ways to reach my current goals").…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, state hope was included so as to document how it augments the prediction of cross-country achievement beyond dispositional hope. This 6-item measure of state hope comprises three agency items and three pathways items (Snyder, Sympson, et al, 1996). The items are reworded from the dispositional Hope Scale so as to tap the present tense (e.g., two agency items are "At the present time, I am energetically pursuing my goals," and "At this time, I am meeting the goals that I have set for myself;" two pathways items are "There are lots of ways around any problem that T am facing now," and "I can think of many ways to reach my current goals").…”
Section: Methodsmentioning
confidence: 99%
“…Expanding on this unidimensional model, Snyder and his colleagues (Snyder, 1994a(Snyder, , 1994bSnyder, Harris, et al, 1991;Snyder, Sympson, et al, 1996) have suggested that goal-directed thinking is made up of two necessary components. First, there is pathways thinking, which reflects the person's capacity to conceptualize one or more avenues by which to arrive at the desired goal.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, relative to the other POB concepts in the CHOSE framework (see Luthans, 2002a), hope has been given the least attention. Yet, because hope meets the POB criteria of being state-like (as well as dispositional, see Snyder, 2000) and thus open to development (see Luthans & Jensen, 2002a for specific human resource developmental guidelines), has a valid measure of 'State Hope' (Snyder et al, 1996), and at least considerable indirect and beginning direct evidence of being related to leadership effectiveness and employee performance, hope would seem to be exactly the type of positive psychological capacity for OB that is needed to be further explored and applied. POSITIVE ORGANIZATIONAL BEHAVIOR 701 Resiliency as a New POB Capacity…”
Section: Hope As the Most Unique Pob Capacitymentioning
confidence: 99%
“…Because scale length was a concern for the organizational leaders, the 12-item version was used that has 4 items representing hope (2 items representing each of the hope mechanisms of pathways thinking and agentic capacity), 3 items representing efficacy, 2 items representing optimism, and 3 items representing resilience. The PCQ items were adapted from published scales on hope (Snyder et al, 1996), efficacy (Parker, 1998), optimism (Scheier & Carver, 1985) and resilience (Wagnild & Young, 1993). The PCQ has both conceptual (Luthans, Youssef & Avolio, 2007) and psychometric support and has been used in previous published research (Avey, Wernsing & Luthans, 2008;.…”
Section: Mediating Variablementioning
confidence: 99%